THE ROLE OF UROLOGISTS IN MANAGEMENT OF DISORDERS OF SEX DEVELOPMENT - Wahyudi, Ilham; Wahyudi, Irfan; Sumadipradja, Kanadi; Batubara, Jose RL; Rodjani, Arry (Indonesian Journal of Urology, 2012)
Objective: To evaluate disorder of sex development (DSD) profile at Cipto Mangunkusumo Hospital (RSCM), the management profile, and the role of urologist on diagnostic and therapeutic management. Material & method: We retrospectively collected data from medical record of all DSD cases managed by pediatric endocrinologist, urologist, obstetric gynaecologist at RSCM from January 2002 up to December 2009. 2006 IICP criteria was used as classification. The management profile and the role of urologist were evaluated. Results: there were 133 DSD cases with the majority of cases was congenital adrenal hyperplasia (CAH) followed by androgen insensitivity syndrome (AIS). Most of the cases were diagnosed before one year old and other on pubertal period. Karyotyping, laboratory examination, ultrasonography, genitography, uretrocystoscopy, kolposcopy, diagnostic laparascopy were performed as diagnostic management. Gender assignment was performed by multidisciplinary team. Masculinizing surgery, feminizing surgery, and gonadectomy was done as therapeutic management. Conclusion: The majority case on RSCM’s DSD profile was CAH. The management was performed by multidisciplinary team. Gender assignment decision should be based upon thorough diagnostic evaluation. The urologist has important role on diagnostic and therapeutic management. Keywords: Disorder of sex development, diagnostic management, gender assignment, therapeutic management, urologist.